Pengembangan Modul Berbasis Pendekatan Heuristik untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa Pada Materi Peluang Kelas VIII SMP - Setiani, Nining; Saragih, Sehatta; Yuanita, Putri (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2024)
This developmental research is based on the low mathematical problem-solving ability of students. The heuristic approach can be used to guide students in problem-solving, thus the researchers used a heuristic-based module to improve students' mathematical problem-solving skills. The aim of this study is to describe the development process, quality, and effectiveness of the heuristic-based module. The research development, or Research and Development, uses the ADDIE model. The research subjects for module validation were experts in the field of education, while the subjects for practicality and effectiveness were eighth-grade students at SMPN 2 Sabak Auh. Data collection techniques included questionnaires and tests, with qualitative and quantitative data analysis. The feasibility assessment of the module obtained an average percentage of 81.31%, classified as very valid. Students' assessment of the module obtained an average percentage of 81.17%, classified as very practical. Based on the sig value in the sig (2-tailed) column of 0.000, which is smaller than 0.05, Ho is rejected and H1 is accepted, indicating that there is a difference in test results before and after using the module. This shows that learning using the heuristic-based module can improve students' mathematical problem-solving skills.